Digitalne podatkovne zbirke pokrovnosti/rabe tal Slovenije - Rikanovič, Rada (Geologija, 2004)
The most frequently used land cover/used data sets of Slovenia in Geological Survey of Slovenia and their methodologies are presented in the article. Theseare CORINE Land Cover, Statistical land cover/use GIS of Slovenia and Agriculture land use monitoring. They are based on different methodologies, data sources and categorization, but primarily designed for GIS use. Though they all have certain disadvantages, they still represent relevant data for general land use analysis.
Keywords: GIS; podatkovne baze; prostorski podatki; raba prostora; raba tal; Slovenia; Slovenija; vegetacija